Outcome at 2-year of treatment in first-episode psychosis patients who were enrolled in a specialized early intervention program. (September 2020) - Meneghelli, Anna; Barbera, Simona; Meliante, Maria; Monzani, Emiliano; Preti, Antonio; Cocchi, Angelo; Percudani, Mauro
Highlights: Patients with psychosis in an early intervention program improved after 2 years. Improvement of patients with first-episode psychosis was heterogeneous. No predictor was related to the improvement of patients with psychosis. Patients with higher levels of psychopathology require more intensive treatment. Abstract: Treatment in early intervention services (EIS) seems superior to treatment as usual on several outcomes, but the extent of heterogeneity in response is unclear. In this study, treatment response trajectories up to 2 years in first-episode psychosis (FEP) patients enrolled in an Italian early intervention service (EIS) have been quantified. The 24-item Brief Psychiatric Rating Scale (BPRS) was used to quantify treatment response up to 2 years in 129 participants. Conditional growth modeling and latent class growth analysis were used to test changes over time in the BPRS and separation into independent classes over time. Group differences were tested on socio-demographic and clinical variables known to be related to outcome in psychosis. Scores on the BPRS showed a statistically significant decrease in overall scores across all tested models. Four trajectories were identified across 2 years. Most patients showed a progressive decrease in the BPRS scores; a scant fraction showed a more stepped decrease from very high levels of psychopathology. No potential predictor was statistically related to the time course of BPRS scores. Most patients that undergo treatment within an EIS are characterized by amelioration, but patients that have higher baseline scores of psychopathology require more intensive treatment.